Tracing down the Updates on Dengue Virus—Molecular Biology, Antivirals, and Vaccine Strategies - Shiza Malik; Omar Ahsan; Hassan Mumtaz; Muhammad Tahir Khan; Ranjit Sah; Yasir Waheed (Vaccines, 2023)
Background: Nearly half of the world is at risk of developing dengue infection. Dengue virus is the causative agent behind this public healthcare concern. Millions of dengue cases are reported every year, leading to thousands of deaths. The scientific community is working to develop effective therapeutic strategies in the form of vaccines and antiviral drugs against dengue. Methods: In this review, a methodological approach has been used to gather data from the past five years to include the latest developments against the dengue virus. Results: Different therapeutics and antiviral targets against the dengue virus are at different stages of development, but none have been approved by the FDA. Moreover, various vaccination strategies have also been discussed, including attenuated virus vaccines, recombinant subunit vaccines, viral vector vaccines, DNA vaccines, nanotechnology, and plant-based vaccines, which are used to develop effective vaccines for the dengue virus. Many dengue vaccines pass the initial phases of evaluation, but only two vaccines have been approved for public use. DENGVAXIA is the only FDA-approved vaccine against all four stereotypes of the dengue virus, but it is licensed for use only in individuals 6–16 years of age with laboratory-confirmed previous dengue infection and living in endemic countries. Takeda is the second vaccine approved for use in the European Union, the United Kingdom, Brazil, Argentina, Indonesia, and Thailand. It produced sustained antibody responses against all four serotypes of dengue virus, regardless of previous exposure and dosing schedule. Other dengue vaccine candidates at different stages of development are TV-003/005, TDENV PIV, V180, and some DNA vaccines. Conclusion: There is a need to put more effort into developing effective vaccines and therapeutics for dengue, as already approved vaccines and therapeutics have limitations. DENGVAXIA is approved for use in children and teenagers who are 6–16 years of age and have confirmed dengue infection, while Takeda is approved for use in certain countries, and it has withdrawn its application for FDA approval.